Leveraging Cash Mobile-Based Application To Improve The Quality Of Mosque Financial Management System - Putri Aggraeni; Eka Sabrina Mustakim; Raodatul Fadilah; Kurnia Prima Putra (Program Studi Teknik Komputer, 2023)
In the era of technological advancement, the need for ease in data processing has become crucial. Recording mosque funds is one area that requires accurate and reliable information, considering the various types of cash transactions managed by the mosque, such as zakat, sadaqah, infak, wakaf, and others. However, the majority of mosque financial managers still rely on manual methods for recording and calculating finances, using books as reporting tools. This method carries high risks of data and report loss, as well as inefficiency in terms of speed and transparency. Therefore, the